A longitudinal analysis of physical functional disability over the course of juvenile idiopathic arthritis. Issue 8 (26th October 2007) - Magni-Manzoni, S; Pistorio, A; Labò, E; Viola, S; Garcia-Munitis, P; Panigada, S; Visconti, C; Buoncompagni, A; Martini, A; Ravelli, A
Abstract : Objective: To describe the longitudinal course of physical functioning in children with juvenile idiopathic arthritis (JIA) and identify predictors of long-term functional impairment. Methods: Between January 1987 and December 2002, 227 patients had two or more functional ability questionnaires completed by a parent. The total number of questionnaires was 1356 and the follow-up between first and last questionnaire administration was 949.7 patient years. At each questionnaire administration, patients were assigned to one of three functional disability states (1 = no disability; 2 = mild to moderate disability; 3 = severe disability), based on their functional ability score. Predictor variables included sex, onset age, JIA category, age at visit, disease duration, presence of antinuclear antibodies, joint counts, acute phase reactants and initial disability state. Results: Despite patient variability in the course of physical functioning, the following three longitudinal patterns were observed: (1) a stable state of disability throughout the entire study period, with continued absence of disability in 27.8% of patients and persistently moderate disability in 3.5% of patients; (2) a steady improvement (22.9% of patients) or deterioration (5.7% of patients) in disability over time; (3) a fluctuating course of disability, with deterioration and improvement (40.1% of patients). Younger age at disease onset and a greater restricted joint count were the strongest predictors of long-term functional impairment. Conclusion: A wide within-patient and between-patient variability in the longitudinal course of functional disability was found. Children with early disease onset and a greater number of restricted joints had the highest risk of developing long-term physical disability.